Honey-Bearing Potential of Tilia cordata Mill. Forests in the Southern Urals - Sultanova, Rida; Martynova, Maria; Sazgutdinova, Regina (Frontiers in Ecology and Evolution, 2022)
This paper examined the honey-bearing potential of Tilia cordata Mill stands in the Southern Urals using forest management and taxation methods. The studies were conducted in pure and mixed even- and uneven-aged forests with Tilia cordata Mill. in different natural zones of the Southern Urals on the territory of the Republic of Bashkortostan. These were forests of the South Ural forest-steppe region, the forest-steppe region of the European part of Russia, the area of coniferous-deciduous (mixed) forests of the European part of Russia. The research employed the method of laying temporary and permanent trial areas. Tilia corda 2ta Mill. forests on the republic's territory were divided into zones by forest districts. There is a discrepancy between the territorial localization of "nectar" (honey-bearing) linden and designated forest areas, that is, honey-bearing forest areas on the republic's territory. It could be due to the lacking methodology for assigning linden to these categories. The increased rotation age of linden trees to 81-90 years for several decades, a ban on final cutting, reduced annual cut of soft-leaved forests by 15 % enlarged the stocks of overmature forest to 48%. Depending on the age, the number of flowers on one Tilia cordata Mill tree varies from 0 to 60.2 thousand pieces. The maximum amount of nectar is 69.04 kg/ha at 12-day linden flowering. The honey productivity of plants including Tilia cordata Mill., calculated concerning the linden age, its share in the forest composition, the average number of flowers on the tree, nectar per 1 ha of linden and the flowering period ranged from 252.8 to 662.8 kg/ha.